SOCIAL ADVERTISING ON PATRIOTIC TOPICS IN THE CONTEXT OF MASS COMMUNICATIONS - Лелека, Ольга (SWorldJournal, 2024)
The article is devoted to the analysis of social advertising in wartime on patriotic topics. It is determined that the main means of disseminating social advertising in wartime was outdoor advertising, presented on billboards, posters, signs at bus stops.